Theoretical problems related to the attachment of microtubules to kinetochores. - Hill, T L (1985)
A possible model is analyzed for the maintenance of attachment of a shortening microtubule (MT) to a kinetochore. In this model it is assumed that a MT is inserted and held in a sleeve or channel of the outer layer of a kinetochore while subunits are lost from the MT tip through the central layer of the kinetochore. A second problem considered is the elementary bioenergetics of MT growth and shortening, as associated with the presence or absence of a GTP cap on the MT ends. The free-energy source is the hydrolysis of GTP in solution. The third problem discussed is the kinetics of capture of a centrosomal MT by a target (e.g., a kinetochore).